Youth mentoring relationships in context: Mentor perceptions of youth, environment, and the mentor role. (June 2015) - Lakind, Davielle; Atkins, Marc; Eddy, J. Mark
Abstract: Youth mentoring is primarily understood as a relationship between mentor and mentee, yet mentors often enter into home, school, and other community settings associated with youth they serve, and interact regularly with other people in mentees' lives. Understanding how and why mentors negotiate their role as they do remains underexplored, especially in relation to these environmental elements. This qualitative study drew on structured interviews conducted with professional mentors ( N  = 9) serving youth at risk for adjustment problems to examine how mentors' perceptions of their mentees and mentee environments informed their sense of how they fulfilled the mentoring role. Mentors commonly characterized problems youth displayed as byproducts of adverse environments, and individual-level strengths as existing "in spite of" environmental inputs. Perceptions of mentees and their environments informed mentors' role conceptualizations, with some mentors seeing themselves as antidotes to environmental adversity. Mentors described putting significant time and effort into working closely with other key individuals as well as one-on-one with mentees because they identified considerable environmental need; however, extra-dyadic facets of their roles were far less clearly defined or supported. They described challenges associated with role overload and opaque role boundaries, feeling unsupported by other adults in mentees' lives, and frustrated by the prevalence of risks. Community-based mentoring represents a unique opportunity to connect with families, but mentors must be supported around the elements of their roles that extend beyond mentor–mentee relationships in order to capitalize more fully on the promise of the intervention. Highlights: Mentors were interviewed about role facets involving mentees and other individuals. Youth problems, more than strengths, were described as environmental byproducts. Mentors related perceptions of their roles to perceptions of mentees' environments. Mentors work with families was less structured than dyadic role. Challenges related to role overload, opaque boundaries, low support and high risk.